Associations of childhood 25-hydroxyvitamin D2 and D3 and cardiovascular risk factors in adolescence: prospective findings from the Avon Longitudinal Study of Parents and Children. (March 2014) - Williams, Dylan M; Fraser, Abigail; Sayers, Adrian; Fraser, William D; Hyppönen, Elina; Smith, George Davey; Sattar, Naveed; Lawlor, Debbie A
Background: Studies of the associations of circulating total 25-hydroxyvitamin D (25(OH)D) with cardiovascular disease risk factors in adults have reported inconsistent findings. We aimed to compare prospective associations of two analogues of childhood 25(OH)D (25(OH)D2 and 25(OH)D3 ) with cardiovascular risk factors measured in adolescence. Methods and results: We examined associations of childhood (ages 7–12 years) 25(OH)D2 and 25-25(OH)D3 with a range of cardiovascular risk factors (blood pressure, fasting lipids, glucose, insulin and C-reactive protein (CRP)) determined in adolescence (mean age 15.4 years). Data were from 2470 participants of the Avon Longitudinal Study of Parents and Children (ALSPAC), a prospective population-based cohort. After adjustments for age, gender, socioeconomic position and BMI, there were no associations of 25(OH)D2 with cardiovascular risk factors. There was a positive association of season-adjusted (and unadjusted) 25(OH)D3 with high-density lipoprotein cholesterol (HDL-C) (mean change per doubling of 25(OH)D3 : 0.03 mmol/l; 95% confidence interval (CI): 0.001 to 0.05, p  = 0.02) and an inverse association with fasting insulin (relative difference of −4.59% per doubling; 95% CI: −8.37 to −0.59, p  = 0.03). Participants with total 25(OH)D concentration <50 nmol/l had 0.04 mmol/l lower HDL-C (95% CI: −0.07 to −0.01) and 5.54% higher fasting insulin (95% CI: 0.82 to 10.47) compared with participants with total 25(OH)D ≥72 nmol/l. Conclusions: In the first prospective study of children/adolescents, we have shown that higher 25(OH)D3 concentrations in childhood are associated with higher levels of HDL-C and lower fasting insulin in adolescence.